Programa de formación educativa para aumentar el índice de actividad física moderada a vigorosa en profesores de educación física (Educational training program to increase the moderate to vigorous physical activity index in physical education teachers) - Hall-López, Javier Arturo (Retos, 2021)
Abstract. Objective: To design and evaluate a training program to increase the moderate to vigorous physical activity index in physical education teachers. Method: the volunteer subjects participated in the educational training program whose goal was to obtain competences on how to create a pedagogical climate in physical education class oriented to the participation of students in moderate to vigorous physical activity at least 50% of the class evaluated quantitatively using the system for observing fitness instruction time (SOFIT), during their university studies and when they have graduated as physical education teachers. Results: The physical activity index increased from 36.6% to 61.2%. Conclusions: The application of the program showed effectiveness with didactic strategies to involve the student in moderate to vigorous physical activity as established by the World Health Organization. Resumen. Objetivo: Diseñar y evaluar un programa de formación educativa para aumentar el índice de actividad física moderada a vigorosa en profesores de educación física. Método: los sujetos voluntarios participaron en el programa de formación que tuvo como meta obtener competencias sobre cómo crear un clima pedagógico en la clase de educación física orientado a la participación de los estudiantes en actividad física moderada a vigorosa por lo menos el 50% de la clase evaluado de manera cuantitativa mediante el sistema para observar el tiempo de instrucción de actividad física (SOFIT), durante sus estudios universitarios y al ser egresados como profesores de educación física. Resultados: el índice de actividad física se incrementó de 36.6% a 61.2%. Conclusiones: La aplicación del programa mostro efectividad con estrategias didácticas para involucrar al alumno en actividad física moderada a vigorosa como lo establece la Organización Mundial de la Salud.